Computational molecular characterization of p53 and Human TLRs interactions - JahoorAlam, Mohammad; Bardakci, Fevzi; Anjum, Sadia; Mir, Shumayla Rasheed; Ahmad, Irfan; Saeed, Mohd (Cellular and Molecular Biology, 2022)
Toll-like receptors (TLRs) are one of the major sensors to regulate innate immunity. It is present in inactive form within immune cells. However, after recognizing the conserved region of the foreign body, it gets activated by the foreign body, such as bacteria, viruses, fungus, etc. Recently, it is reported that apart from participating in innate immunity, these TLRs also play an important role in apoptosis and cancer. Moreover, very few reported that it is cross-talk with p53 protein within the cell. P53 protein is a transcription factor for many cellular proteins involved in cellular transduction. It directly as well as indirectly regulates a wide variety of cellular processes such as apoptosis, senescence, cell cycle arrest, differentiation, and DNA repair and replication and cancer dynamics. Various studies reported genetic level interaction between p53 and TLRs. However, molecular interaction studies are still few reported. In the present work, we computationally characterized molecular interaction between p53 and toll-like receptors. We used open web resources for docking and analyzing the data. Our molecular docking and molecular dynamics simulation results suggest that there is a significant interaction between p53 and toll-like receptors. The study could important for the possible therapeutic intervention.